Methodological strategies for the useof ICT tools in the teaching-learning process of Natural Sciences in elementary school student - Burbano Hurtado, Johana Alexandra (SATHIRI, 2024)
The objective of the present research was to propose methodological strategies for the use of ICT tools in the teaching-learning process of Natural Sciences in elementary school students of the “Gran Colombia"; Educational Unit, located in the city of Tulcán, Province of Carchi. The research assumed a mixed approach, descriptive scope, and integrates documentary and field information. The use of ICT tools in the teaching ofnatural sciences by teachers was diagnosed. For this, an in-depth interview was applied to 5 teachers who teach natural sciences in the institution. Subsequently, a survey was conducted on 50 elementary school students of the institution, using a questionnaire with high reliability (Cronbach ́s alpha = 0.84). The results indicate that teachers apply traditional strategies and the use of ICT tools is very scarce, however, they consider that methodological strategies with ICT tools allow improving teaching processes at different educational levels. On the other hand, technological applications used by students are not used for educational purposes, losing their educational potential. Based on this diagnosis, six strategies were designed that contain the description, design, and application with the purpose of improving the teaching-learning of natural sciences, supported by Problem-Based Learning, Collaborative Learning, and Flipped Learning, and for each of them, the necessary ICT tools were included to obtain meaningful learning through the interaction of teacher and students during their teaching process.
Keywords: Methodological strategies; teaching-learning process; natural sciences; ICT